2010
DOI: 10.1179/174328910x12647080902970
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on mechanical, thermal, viscoelastic and rheological properties of vulcanised EPDM rubber

Abstract: In this study, mechanical, thermal and rheological properties of vulcanised ethylene propylene diene monomer (EPDM) rubber containing different amounts of vulcanising agent, filler, paraffinic oil and stearic acid were compared. Moreover, reaction rate constant of the curing reaction has been calculated from the results of the rheological tests, and relative change of rate constant with the change of additives was studied by a new method. Thermal gravimetric analysis with in situ Fourier transform infrared (FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
(10 reference statements)
1
24
0
Order By: Relevance
“…As pointed out by Gent [7], the tear strength initially increases as the crosslink level increases, but, after reaching a maximum value, it decreases at excessively high crosslink levels, which restrict chain motions so that the tight network is incapable of dissipating much energy, resulting in relatively easy, brittle fracture at low elongation. This is consistent with the results of [21], which showed that increasing the level of vulcanisation agent and thereby crosslink density initially enhances the mechanical properties, but beyond a certain level further increases have the opposite effect. Alternatively, as compared with the use of MD, it can be inferred that the use of MZ and MZD provide lower crosslink levels that favour tear strength.…”
Section: Combinationssupporting
confidence: 82%
“…As pointed out by Gent [7], the tear strength initially increases as the crosslink level increases, but, after reaching a maximum value, it decreases at excessively high crosslink levels, which restrict chain motions so that the tight network is incapable of dissipating much energy, resulting in relatively easy, brittle fracture at low elongation. This is consistent with the results of [21], which showed that increasing the level of vulcanisation agent and thereby crosslink density initially enhances the mechanical properties, but beyond a certain level further increases have the opposite effect. Alternatively, as compared with the use of MD, it can be inferred that the use of MZ and MZD provide lower crosslink levels that favour tear strength.…”
Section: Combinationssupporting
confidence: 82%
“…The results indicated that PPSQ affects volatile products of EPDM and is detected in its formulation by TG/FT-IR. Çavdar et al [7] studied different vulcanizing agent contents by TG/FT-IR. They observed that increasing vulcanizing agent content decreased band intensities of CO and CO 2 and enhanced the thermal stability of EPDM rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Low molecular weight chemical compounds, known as additives, are incorporated in to rubbers to obtain desirable properties [2] . The main additives used in rubbers are antioxidants, vulcanizing agents, accelerators, reinforcing agents, activators, and processing aids.…”
Section: Introductionmentioning
confidence: 99%